The Effect of Effective Cough Education and Chest Physiotherapy on Knowledge and Independence of Parents in Handling Bronchopneumonia Children Using Audiovisual Media at RSUD DR. Abdul Rivai - Kriestian Sugih Budiarto; Umi Kalsum; Gajali Rahman (Formosa Journal of Applied Sciences, 2023)
Children with pneumonia cause the ability of the lungs to expand to decrease so that the body reacts by breathing quickly to prevent hypoxia. The use of media such as audiovisual is believed to be able to stimulate the senses of hearing and sight so that the results obtained are maximized. Using a research design quesy experiment with pre-test and post-test design. A sample of 32 respondents was taken by Consecutive Sampling. Data analysis was performed with the Wilcoxon test. The results of hypothesis testing with the Wilcoxon test obtained a p-value pre-test and post-test for the level of parental knowledge of 0.000 (p-value <0.05) and a p-value for pre-test and post-test for the level of parental independence of 0.039 (p- value < 0.05). There is an effect of effective cough education and chest physiotherapy on parents' knowledge and independence.